The development of methodological approaches to the residential real estate segmentation by the affordability criterion - Muller Pavel; Chepeleva Kristina; Saenko Irina; Shmeleva Zhanna (E3S Web of Conferences, 2020)
The article proposes to consider the issues of the residential real estate objects affordability from the position of differentiation by market segments, taking into account differences in the parameters of objects, as well as differences in the cost of objects. The issues of housing affordability are considered both in terms of improving housing conditions through the acquisition and the rent. When calculating affordability coefficients, it is proposed to differentially take into account the difference in the income of the population different groups. The matrix of housing affordability in the Krasnoyarsk market was formed from the point of view of the purchasing and renting possibility. The presented methodological approaches to determining the affordability of the residential real estate objects based on segmentation allow to improve the understanding of the processes taking place in the market, and adjust the main directions of the state’s housing policy. This is an opportunity for the construction business and residential rental sector to implement their offers with a clear focus on the target audience, taking into account the specificity of the local market.